Implications of Nutritional Management on Fatty Acid Profiles of Southern White Rhinoceroses (Ceratotherium simum simum) Housed at Two Zoological Institutions - Jordan Wood (MDPI AG, 2021)
Southern white rhinoceroses (Ceratotherium simum simum) are African megaherbivores that are considered near threatened by the International Union for the Conservation of Nature. The fatty acid circulating values of these animals have not been thoroughly investigated. Fatty acids are critical for immune, heart, skin, and reproductive health, and may have a significant impact on the management and conservation of this species. Published data on fatty acids in this species is limited to incomplete profiles with very few animals in managed environments. The objectives of this research were to provide novel fatty acid percentage profiles for managed healthy southern white rhinoceroses, as well as to provide comparisons between two zoological institutions with differences in diet and climate during two distinct pasture growth periods. Whole blood samples were collected as dried blood spots from six rhinoceroses at the North Carolina Zoo (NC Zoo) and five rhinoceroses at Busch Gardens Tampa (BGT) in the low growth period (February to April) of 2019 and during the high growth period (July to September) of 2020. Fatty acid results indicated numerous differences when comparing the institutions within the same growth period and when comparing the same institution between its two growth periods. Most noteworthy were the higher levels of α-linolenic acid (18:3w3) and total omega-3 fatty acids and the lower linoleic acid (18:2w6), total omega-6 fatty acids, and omega-6 to omega-3 ratio found in the BGT population in both growth periods. This study provides novel percentages of fatty acids in managed southern white rhinoceroses and data on how fatty acid profiles may be altered between two housing locations via dietary differences in hay type and quantity, pasture availability via season, and pellet inclusion levels.